2021
DOI: 10.1097/as9.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Ileal Pouch-anal Anastomosis Complications and Pouch Failure

Abstract: Objective: This systematic review aims to assess the incidence of pouch failure and the correlation between ileal pouch-anal anastomosis (IPAA)-related complications and pouch failure. Background: Previous studies demonstrated wide variation in postoperative complication rates following IPAA. Methods: A systematic review was performed by searching the MEDLINE, EMBASE, and Cochrane Library databases for studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 69 publications
2
18
1
Order By: Relevance
“…Heimann et al [28] reported that 9% of UC patients undergoing IPAA developed a perianal fistula, which is slightly lower than the cumulative rate of 12% reported in our study. However, unlike our study in which a 6‐month window from ileostomy closure was used, Heuthorst et al [27] arbitrary defined early perianal fistula as the diagnosis of a perianal fistula within 5 years from the IPAA index surgery. Therefore, they were unable to discern which patients developed fistulas as part of an early postoperative complication, such as anastomotic dehiscence, from fistulas arising as part of CDLPC.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Heimann et al [28] reported that 9% of UC patients undergoing IPAA developed a perianal fistula, which is slightly lower than the cumulative rate of 12% reported in our study. However, unlike our study in which a 6‐month window from ileostomy closure was used, Heuthorst et al [27] arbitrary defined early perianal fistula as the diagnosis of a perianal fistula within 5 years from the IPAA index surgery. Therefore, they were unable to discern which patients developed fistulas as part of an early postoperative complication, such as anastomotic dehiscence, from fistulas arising as part of CDLPC.…”
Section: Discussionmentioning
confidence: 89%
“…The overall pouch failure rate described in our study (6.1%) is close to that described in a more recent meta‐analysis that reviewed IPAA complications and pouch failure. This meta‐analysis reported a pooled pouch failure rate of 7.7% for studies with a median follow‐up of five or more years and 10.3% for studies with a median follow‐up of 10 or more years [27]. However, this meta‐analysis did not exclude pouch failures not attributed to CDLPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients undergoing pouch surgery have a good outcome post-operatively, but a significant minority have complications following surgery that may lead to pouch failure. A recent meta-analysis demonstrated that the long-term pouch failure rate is 10% after 10 years of follow-up [5]. Pouch surgery is a quality-of-life operation.…”
Section: E D I T O R I a L Editorial: Regionalisation Of Ileoanal Pou...mentioning
confidence: 99%
“…3 4 Two recent meta-analyses with more than 20,000 UC patients each, showed a prevalence of PF of 5% at 5 years and 9 to 10% at 10 years from the operation. 5 6 In this review article we describe the presentation, workup, diagnosis treatment, and outcomes of PF.…”
mentioning
confidence: 99%